Juvenile Justice After Graham v. Florida: Keeping Due Process, Autonomy, and Paternalism in Balance - Kristin Henning (Washington University Journal of Law & Policy, 2012)
Legal disputes involving children invariably evoke a complex matrix of issues such as child and adolescent capacity, individual rights and autonomy, parental authority, and in the criminal justice context—diminished culpability for a minor‘s actions. While it is difficult to identify a clear and cohesive jurisprudence regarding the balance between children‘s autonomy and children‘s vulnerability across Supreme Court cases, a series of cases over the last decade, including Roper v. Simmons, Graham v. Florida, and J.D.B. v. North Carolina, offer a more consistent view of children as vulnerable, malleable, and in need of protection, at least in the criminal and delinquency context. In each of these cases, the Court solidly reaffirms the view that youth lack maturity and are more "susceptible" to negative influences. Specifically, this Essay considers Graham‘s impact on the ever-changing philosophy of the juvenile justice system, which is often at a crossroads between its rehabilitative, punitive, and due process agendas. The Supreme Court‘s affirmation in Graham of research on the important developmental differences between juveniles and adults may reinvigorate the rehabilitative goal of traditional juvenile courts and challenge the recent trend toward more punitive juvenile justice policies. However, it may also signal a shift back to a more paternalistic approach to children‘s law and policy, including reduced autonomy for youth and greater state intervention in the lives of children.
Keywords: Graham v. Florida 130 S. Ct. 2011 (2010); Cruel and unusual punishment; Due process of law; Juvenile offenders; Paternalism; United States